Post-traumatic growth in caregivers of children hospitalized in the PICU due to traffic accident: a qualitative study - Zhi Hong Ni; Hai Tao Lv; Jin Hua Wu; Fang Wang (BMC Nursing, 2023)
Abstract Background Globally, tens of millions of children are hospitalized every year for non-fatal traffic accident injuries, being confronted with an injured child can be extremely stressful for parents. Understandably, a significant level of psychological distress may ensue. Traumatic losses may lead parents to find new insights in life and develop a greater sense of spirituality and strength. Method Semi-structured interviews were conducted with caregivers of children who were hospitalized in the pediatric intensive care unit (PICU) with traffic accident injuries at children’s hospitals in China between January and June 2022. Caregivers were selected using a purposive sampling method until no new data were generated (n = 24). Results We identified eleven sub-themes and four higher-order themes based on these sub-themes: (1) changes in their life philosophy, (2) personal strength enhancement, (3) relationship improvements, and (4) effective responses. The findings of our research contribute to a better understanding of the psychological status of the caregivers of children injured by traffic accidents. Conclusion Professionals should guide caregivers from a positive perspective, stimulate their strengths and potential, increase personnel support and communication, promote positive coping, formulate targeted management countermeasures to improve the PTG level of caregivers, and develop strategies to maintain stable mental health and well-being.